2011
DOI: 10.5539/jsd.v5n1p55
|View full text |Cite
|
Sign up to set email alerts
|

A Second Look: Stakeholders’ Perceptions of Some Issues in Design-Bid-Build Procurement Practice in Nigeria

Abstract: The construction product is an outcome of many procurement possibilities, among which the most dominant has been the design-bid-build (otherwise called the traditional) method. The procurement method's real or perceived drawbacks have warranted or even been rationalized for the emergence of alternative methods. Yet there is a continued use of the method in both private and public sector projects in Nigeria. This study thus sought to investigate stakeholders' perception on the use of the traditional method. 241… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Such strategies include Traditional, Design and Build, Project Management, Direct Labour and Labour-only. Studies of Ogunsanmi, Iyagba and Omirin (2001), Ibiyemi, Adenuga and Odusami (2005), Babatunde, Opawole and Ujaddigbe (2010) and Dada (2012) have all confirmed the use of these methods in Nigeria. Similarly, studies of Rowlinson (1987), Naoum and Langford (1987), Grierson (1988), Franks (1990), Bennett (1992), Hutchinson and Putt (1992) as cited in Ogunsanmi, (2001) also confirm the use of these methods for project delivery elsewhere in the World.…”
Section: Construction Procurement Strategies In Usementioning
confidence: 87%
See 1 more Smart Citation
“…Such strategies include Traditional, Design and Build, Project Management, Direct Labour and Labour-only. Studies of Ogunsanmi, Iyagba and Omirin (2001), Ibiyemi, Adenuga and Odusami (2005), Babatunde, Opawole and Ujaddigbe (2010) and Dada (2012) have all confirmed the use of these methods in Nigeria. Similarly, studies of Rowlinson (1987), Naoum and Langford (1987), Grierson (1988), Franks (1990), Bennett (1992), Hutchinson and Putt (1992) as cited in Ogunsanmi, (2001) also confirm the use of these methods for project delivery elsewhere in the World.…”
Section: Construction Procurement Strategies In Usementioning
confidence: 87%
“…criteria. Study of Dada (2012) is on Traditional procurement and it indicates that the method has been long used for both public and private projects. It further considers the perceptions of stakeholders on issues of Traditional procurement.…”
Section: Introductionmentioning
confidence: 99%
“…Different studies have confirmed the use of various types of procurement methods for project delivery in Nigeria. Studies of Ogunsanmi, Iyagba and Omirin (2003), Ojo, Adeyemi and Fagbenle (2006), and Dada (2012) all confirm the use of Traditional, Design and Build, Project Management, Construction Management, Labouronly, Direct Labour and other types such as Alliancing, Partnering and Joint Ventures procurements in the Nigerian construction industry. The use of these procurement methods can significantly affect the performance of most projects.…”
Section: Introductionmentioning
confidence: 88%
“…The construction industry in Nigeria is fast growing with its activities having a direct bearing on the national economy. According to Dada (2012), the industry is important for the growth and development of the country. This is evident in its provision and maintenance of infrastructures.…”
Section: Introductionmentioning
confidence: 99%